Tempering and Intercritical Annealing of Air‐Hardening 4 wt% Medium Manganese Steels. Issue 11 (22nd May 2021) - Gramlich, Alexander; Bleck, Wolfgang
Abstract : The mechanical properties after tempering and intercritical annealing of medium manganese steels with 4 wt% Mn for forging applications are presented. After forging with subsequent air cooling, heat treatments were performed, specifically tempering from 250 and 450 °C and intercritical annealing between 600 and 675 °C. Tensile properties, Charpy V‐notch impact toughness, and hardness were determined and compared with microstructural features characterized by metallography and synchrotron measurements, leading to the classification of six different heat treatment stages for medium manganese steels. Furthermore, the effects of different alloying additions (boron 0.0016–0.0057 wt%, molybdenum 0.2 wt%, and aluminum 0.5 wt%) are discussed with respect to the mechanical properties. It is shown that boron increases the impact toughness more effectively in the tempering regime, while the molybdenum alloyed samples exhibit higher toughness after intercritical annealing. Most of the materials and heat treatment states follow the inverse relationship between toughness and strength, while the aluminum alloyed samples show a superior toughness after tempering. Abstract : The mechanical properties of 4 wt% medium manganese steels after different heat treatments are investigated. While the air‐hardened as well as tempered condition is characterized by high strengths and comparatively low ductilities, this balance is reversed for the intercritically heat‐treated samples. This trade‐off can be prevented by the alloying of aluminum, leading to a superior property balance.